2008
DOI: 10.1007/s00125-008-1125-6
|View full text |Cite
|
Sign up to set email alerts
|

Glucose increases hepatic lipase expression in HepG2 liver cells through upregulation of upstream stimulatory factors 1 and 2

Abstract: Aims/hypothesis Elevated hepatic lipase (HL, also known as LIPC) expression is a key factor in the development of the atherogenic lipid profile in type 2 diabetes and insulin resistance. Recently, genetic screens revealed a possible association of type 2 diabetes and familial combined hyperlipidaemia with the USF1 gene. Therefore, we investigated the role of upstream stimulatory factors (USFs) in the regulation of HL. Methods Levels of USF1, USF2 and HL were measured in HepG2 cells cultured in normal-or high-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 51 publications
(97 reference statements)
0
30
0
Order By: Relevance
“…Similar induction of shp mRNA and protein level was observed in HepG2 cells (data not shown). Previous reports have demonstrated that USF-1 increased glycolysis via activation of key glycolytic enzyme genes, L-PK and GK gene promoters (1,14,16). As a positive control, Ad USF-1 treatment was shown to induce l-pk and gk mRNA expression significantly in primary hepatocytes (Fig.…”
Section: Induction Of Shp Gene Expression By Hgf Is Specificallymentioning
confidence: 74%
See 3 more Smart Citations
“…Similar induction of shp mRNA and protein level was observed in HepG2 cells (data not shown). Previous reports have demonstrated that USF-1 increased glycolysis via activation of key glycolytic enzyme genes, L-PK and GK gene promoters (1,14,16). As a positive control, Ad USF-1 treatment was shown to induce l-pk and gk mRNA expression significantly in primary hepatocytes (Fig.…”
Section: Induction Of Shp Gene Expression By Hgf Is Specificallymentioning
confidence: 74%
“…USF-1 protein level is found to be increased in feeding (28) and high glucose conditions (14), correlated to the decrease in hepatic gluconeogenesis under these conditions. Therefore, the induction of SHP gene expression by USF-1 in primary hepatocytes, as demonstrated in this study, may provide a plausible link connecting the decrease of PEPCK and Glc-6-Pase gene expression by SHP to USF-1 expression pattern.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…Chronic hyperglycemia is capable of exerting adverse effects on hepatic cells, i.e., metabolic disorders of glucose, lipid, and energy, breakdown of redox equilibrium, and dysregulation of several cellular processes, which can also lead to hepatic insulin resistance [28,29]. In the present study, the HepG2 cell line has been used as an in vitro model system aiming to investigate the effects of prolonged elevated glucose.…”
Section: Discussionmentioning
confidence: 99%